2008
DOI: 10.1523/jneurosci.1812-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic and Postsynaptic Amplifications of Neuropathic Pain in the Anterior Cingulate Cortex

Abstract: Neuropathic pain is caused by a primary lesion or dysfunction in the nervous system. Investigations have mainly focused on the spinal mechanisms of neuropathic pain, and less is known about cortical changes in neuropathic pain. Here, we report that peripheral nerve injury triggered long-term changes in excitatory synaptic transmission in layer II/III neurons within the anterior cingulate cortex (ACC). Both the presynaptic release probability of glutamate and postsynaptic glutamate AMPA receptor-mediated respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
332
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 332 publications
(354 citation statements)
references
References 75 publications
20
332
0
2
Order By: Relevance
“…Animal studies of the ACC not only confirm the importance of ACC in nociception (Vogt, 2005;Zhuo, 2008Zhuo, , 2011, but also reveal molecular mechanisms for chronic pain (Zhuo, 2006(Zhuo, , 2008. While peripheral injury triggers activity-dependent immediate early genes (Zhuo, 2006(Zhuo, , 2011 and induces long-term potentiation (LTP) of excitatory synaptic responses in the ACC neurons (Wei and Zhuo, 2001;Xu et al, 2008), inhibition or genetic deletion of key molecules required for triggering LTP produces analgesic effects in animal models of chronic pain (Wei et al, 2002;Wu et al, 2005b;Wang et al, 2011). Recently, protein kinase M (PKM) has been identified as a key enzyme required to maintain such injury-related LTP (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Animal studies of the ACC not only confirm the importance of ACC in nociception (Vogt, 2005;Zhuo, 2008Zhuo, , 2011, but also reveal molecular mechanisms for chronic pain (Zhuo, 2006(Zhuo, , 2008. While peripheral injury triggers activity-dependent immediate early genes (Zhuo, 2006(Zhuo, , 2011 and induces long-term potentiation (LTP) of excitatory synaptic responses in the ACC neurons (Wei and Zhuo, 2001;Xu et al, 2008), inhibition or genetic deletion of key molecules required for triggering LTP produces analgesic effects in animal models of chronic pain (Wei et al, 2002;Wu et al, 2005b;Wang et al, 2011). Recently, protein kinase M (PKM) has been identified as a key enzyme required to maintain such injury-related LTP (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…Peripheral injuries, such as nerve injury or inflammation, trigger synaptic potentiation in the ACC pyramidal cells. Both presynaptic enhancement of glutamate release and postsynaptic amplification of AMPA receptor-mediated responses contribute to the potentiation (Xu et al, 2008;Zhuo, 2008;Li et al, 2010). For peripheral amputation, LTPlike potentiation has been reported in rats under anesthesia in vivo (Wei and Zhuo, 2001).…”
Section: Loss Of Cortical Ltd After Amputationmentioning
confidence: 99%
“…2C). It has been reported that peripheral nerve injury triggers long-term potentiation in the anterior cingulate cortex (Xu et al, 2008). Therefore, we investigated the fluorescence responses in the cortical areas medial to the response center.…”
Section: Somatic Cortical Potentiation After Peripheral Nerve Cuttingmentioning
confidence: 98%
“…the ratio of the second peak amplitude over the first peak amplitude induced by paired pulse stimulation). Analysis of PPRs is a classic approach to determine the transmitter release probability from presynaptic terminals (27,(41)(42)(43)(44). A decrease of PPR indicates an increased probability of neurotransmitter release from presynaptic terminals.…”
Section: Endogenous Il-1␤ In Neuropathic Rats Enhances Glutamate Relementioning
confidence: 99%